METASTATIC CLEAR CELL RENAL CARCINOMA MIMICKING AS A PAPILLARY THYROID CANCER: A CASE REPORT - Aribon, Pamela Ann; Maningat, Maria Patricia Deanna (Journal of the ASEAN Federation of Endocrine Societies, 2022)
INTRODUCTION The thyroid gland is a vascular organ, however, metastatic cancer to the thyroid is a rare and uncommon clinical finding. These tumors can lead to diagnostic difficulties as they can mimic a primary thyroid gland tumor. CASE We present a 58-year-old Filipino woman with a history of Renal Cell Carcinoma (RCC), who underwent nephrectomy 13 years ago, referred due to a PET scan finding of a solitary right thyroid nodule. Fine needle aspiration biopsy of the thyroid nodule was done which was suggestive of a Papillary Thyroid Cancer. She then underwent total thyroidectomy however histopathology revealed right thyroid gland consistent with metastatic clear cell renal cell carcinoma. CONCLUSION In patients presenting with thyroid nodule/s, with a history of malignant disease, relapse or progression of the malignancy within the thyroid must be considered until proven otherwise. If a patient with a history of nephrectomy for RCC subsequently has a solitary thyroid mass, one should consider isolated thyroid metastasis as well as a primary thyroid tumor. Fine Needle Aspiration Biopsy is not enough to diagnose metastatic renal cell carcinoma to the thyroid, a history of clear cell renal carcinoma or multifocal growth pattern and clear cell appearance of cytoplasm by histopathology should be considered. Preoperative distinction between primary and secondary thyroid tumors is difficult. Immunohistochemistry is essential for confirming the diagnosis.